Fear of Missing Out Sebagai Prediktor Psychological Well-Being pada Karyawan Fresh Graduate Perusahaan X - Adyatma Susilo Nugroho; Sutarto Wijono (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Fear of Missing Out is a psychological condition characterized by anxiety about missing valuable experiences or opportunities. This study aims to determine whether Fear of Missing Out is a significant predictor of psychological well-being among fresh graduate employees at Company X. The research employed a quantitative approach with a simple regression design and involved 63 participants selected through purposive sampling. The instruments used were the Workplace Fear of Missing Out Scale and Ryff’s Psychological Well-Being Scale. The results showed that Fear of Missing Out significantly predicted psychological well-being. These findings indicate the importance of managing Fear of Missing Out to support employees’ psychological well-being.